Facilitators, barriers and opportunities in workplace wellbeing: A national survey of emergency department staff. (July 2021) - Anderson, Natalie; Pio, Fofoa; Jones, Peter; Selak, Vanessa; Tan, Eunicia; Beck, Sierra; Hamilton, Suzanne; Rogan, Alice; Yates, Kim; Sagarin, Mark; McLeay, Adam; MacLean, Alistair; et al.
Highlights: Emergency clinician burnout rates are high and associated with negative patient outcomes. 1372 New Zealand ED staff were surveyed about their workplace wellness. Participants valued a supportive team, excellent patient care and education. Wellness interventions are needed at an organisational, as well as individual level. Abstract: Introduction: Emergency department (ED) staff face daily exposure to the illness, injury, intoxication, violence and distress of others. Rates of clinician burnout are high and associated with poor patient outcomes. This study sought to measure the prevalence of burnout in ED personnel as well as determine the important facilitators of and barriers to workplace wellbeing. Method: An anonymous online survey including six open-ended questions on workplace wellbeing was completed by 1372 volunteer participants employed as nurses, doctors, allied health or nonclinical roles at 22 EDs in Aotearoa, New Zealand in 2020. Responses to the questions were analysed using a general inductive approach. Results: The three key themes that characterise what matters most to participants' workplace wellbeing are: (1) Supportive team culture (2) Delivering excellent patient-centred care and (3) Professional development opportunities. Opportunities to improve wellbeing also focused on enhancements in these three areas. Conclusion: In order to optimise workplace wellbeing, emergency departments staff value adequate resourcing for high-quality patient care, supportive and cohesive teams and professional development opportunities. Initiatives in these areas may facilitate staff wellbeing as well as improving safety and quality of patient care.